2015
DOI: 10.1371/journal.pgen.1005165
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Gene-Based Rare Variant Methods to Detect Disease-Associated Variation and Test Hypotheses About Complex Disease

Abstract: Genome and exome sequencing in large cohorts enables characterization of the role of rare variation in complex diseases. Success in this endeavor, however, requires investigators to test a diverse array of genetic hypotheses which differ in the number, frequency and effect sizes of underlying causal variants. In this study, we evaluated the power of gene-based association methods to interrogate such hypotheses, and examined the implications for study design. We developed a flexible simulation approach, using 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
146
1
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 131 publications
(152 citation statements)
references
References 30 publications
4
146
1
1
Order By: Relevance
“…We note that our results contrast those of Moutsianas et al (2015), who used the Eyre-Walker (2010) model and found higher power for RVATs when rare alleles explain a large fraction of trait variance. However, we also note that their study predominantly focused on a model of binary traits that have unidirectional effects, whereas we have focused on a model of quantitative traits under stabilizing selection with bidirectional effects.…”
Section: Evolutionary Forces and Rare Variant Detectioncontrasting
confidence: 99%
See 1 more Smart Citation
“…We note that our results contrast those of Moutsianas et al (2015), who used the Eyre-Walker (2010) model and found higher power for RVATs when rare alleles explain a large fraction of trait variance. However, we also note that their study predominantly focused on a model of binary traits that have unidirectional effects, whereas we have focused on a model of quantitative traits under stabilizing selection with bidirectional effects.…”
Section: Evolutionary Forces and Rare Variant Detectioncontrasting
confidence: 99%
“…However, we note that SKAT-O was specifically designed to retain power in both situations (equal and unequal proportions of trait-increasing/trait-decreasing variants) (Lee et al 2012a,b), so we do not expect that the main results of the paper (i.e., that selection strength and growth rate alter architecture and power) are affected by this choice. Moreover, a recent study examined the Pearson correlation between P-values reported by a wide range of RVATs (Moutsianas et al 2015), and found that SKAT-O is highly correlated to SKAT (0.93), C-ALPHA (Neale et al 2011) (0.92), and KBAC (Liu and Leal 2010) (Price et al 2010) (0.63), and BURDEN (https://atgu.mgh. harvard.edu/plinkseq/) (0.77).…”
Section: Power Of Rare Variant Testsmentioning
confidence: 99%
“…Even though correction for population stratification is extensively enabled in our study, rare variant association analysis is limited by the current sample size [74]. Because not all genes and not all noncoding regions could be selected in our study, whole-genome sequencing would be a desirable next step.…”
Section: Discussionmentioning
confidence: 99%
“…In the case of common variants, the requirement for large samples is due to the small effect sizes expected--typically an allelic odds ratio of less than 1.20. In the case of rare variants, effect sizes may be larger, but their rarity again entails large sample sizes to allow detection of a sufficient number of risk variant carriers (Moutsianas et al, 2015;Zuk et al, 2014). Gene-environment interaction (G × E) studies examine whether the effect of a genetic variant is modified by an environmental exposure.…”
Section: The Toolkit Of Psychiatric Geneticsmentioning
confidence: 99%